2006
DOI: 10.1016/j.pbb.2006.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Anxiolytic-like actions of buspirone in a runway model of intravenous cocaine self-administration

Abstract: In previous work from our laboratory, rats traversing a straight alley for a reward of IV cocaine have been observed to develop ambivalence about entering the goal box. Over trials, animals repeatedly run toward the goal box, stop at the entry point, and then retreat back toward the start box. This unique pattern of retreat behavior has been shown to reflect a form of "approach-avoidance conflict" that stems from the subjects' concurrent positive (cocaine reward) and negative (cocaine-induced anxiety) associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 73 publications
2
26
1
Order By: Relevance
“…Cocaine is also a potent reuptake inhibitor at the serotonergic (5-hydroxytryptamine; 5-HT) transporter (Filip et al, 2005; Koe, 1976; Ritz et al, 1990) and while manipulations of 5-HT systems have at times produced contradictory and inconclusive results in behavioral tests of anxiety (e.g., Handley et al, 1993) there is a growing literature implicating 5-HT neurons emanating from the dorsal raphé nucleus in the behavioral response to a variety of stressors and anxiogenic drugs (e.g., Abrams et al, 2005; Chaouloff, 2000; Reuter and Jacobs, 1996; Rex et al, 2005; Sena et al, 2003). Indeed, we have previously reported that interfering with 5-HT function via lesion or pharmacological manipulations reduced the aversive response to cocaine while leaving the positive/rewarding effects intact (e.g., Ettenberg and Bernardi, 2006; 2007; Ettenberg et al, 2011). Such results nicely compliment those observed here and suggest a role for 5-HT signaling in the anxiogenic actions of cocaine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cocaine is also a potent reuptake inhibitor at the serotonergic (5-hydroxytryptamine; 5-HT) transporter (Filip et al, 2005; Koe, 1976; Ritz et al, 1990) and while manipulations of 5-HT systems have at times produced contradictory and inconclusive results in behavioral tests of anxiety (e.g., Handley et al, 1993) there is a growing literature implicating 5-HT neurons emanating from the dorsal raphé nucleus in the behavioral response to a variety of stressors and anxiogenic drugs (e.g., Abrams et al, 2005; Chaouloff, 2000; Reuter and Jacobs, 1996; Rex et al, 2005; Sena et al, 2003). Indeed, we have previously reported that interfering with 5-HT function via lesion or pharmacological manipulations reduced the aversive response to cocaine while leaving the positive/rewarding effects intact (e.g., Ettenberg and Bernardi, 2006; 2007; Ettenberg et al, 2011). Such results nicely compliment those observed here and suggest a role for 5-HT signaling in the anxiogenic actions of cocaine.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, DA signaling within the mesolimbic system has been shown to be integral for the demonstration of stress-induced reinstatement of cocaine seeking following a period of drug abstinence (Capriles et al, 2003; McFarland et al, 2004; Wang et al, 2005; Xi et al, 2004). It should be noted, however, that previous research has identified other catecholamine systems as potential substrates for the expression of cocaine’s negative/anxiogenic effects (Ettenberg et al, 2011; Ettenberg and Bernardi, 2006; Ettenberg and Bernardi, 2007; Schank et al, 2008; Smith and Aston-Jones, 2008; Wenzel et al, 2012). Thus the precise nature of the neuronal systems underlying these effects of cocaine remains unclear.…”
Section: Introductionmentioning
confidence: 98%
“…In addition to food+shock experiments, retreat behaviors have also been shown to occur in animals running for drug reinforcers known to have mixed positive+negative consequences (e.g., cocaine; Ettenberg and Geist 1991, 1993; Geist and Ettenberg 1997; Guzman and Ettenberg 2004). Additionally, pretreatment with anxiolytic drugs dose-dependently reduce retreat frequency in the runway – e.g., diazepam (Ettenberg and Geist 1991; Geist and Ettenberg 1997), alcohol (Knackstedt and Ettenberg 2005), heroin (Guzman and Ettenberg 2004), and buspirone, a partial 5-HT(1A) agonist (Ettenberg and Bernardi 2006). …”
Section: Introductionmentioning
confidence: 99%
“…The dose of 1 mg/kg i.v. cocaine was chosen based upon the results of previous runway work from our laboratory (Raven et al 2000; Ettenberg 2004; Ettenberg and Bernardi 2006; Wenzel et al 2011; 2014). …”
Section: Methodsmentioning
confidence: 99%
“…The rationale for examining the functional role of 5-HT with respect to cocaine’s anxiogenic effects stems from the fact that 5-HT has been implicated in the development and expression of anxiety-like behaviors (Watson and Mann 2000; Sena et al 2003; Abram et al 2005) and that cocaine has significant affinity for the 5-HT transporter (Cunningham et al 1992a, 1992b; Walsh and Cunningham 1997; Filip et al 2004). Additionally, in our own prior studies, inactivation of the 5-HT cell bodies within the dorsal raphé nucleus (Ettenberg et al 2011) or treatment with the anxiolytic 5-HT 1A partial agonist, buspirone, both reduced approach-avoidance “retreats” in the runway (Ettenberg and Bernardi 2006). Buspirone was also effective at selectively attenuating the delayed negative effects of cocaine without modifying the drug’s initial positive effects in a Conditioned Place Test (Ettenberg and Bernardi 2007).…”
Section: Introductionmentioning
confidence: 98%